Microbe-engaged synthesis of carbon dot-decorated reduced graphene oxide as high-performance oxygen reduction catalysts. Issue 19 (20th April 2016) - Zhou, Lihua; Fu, Peng; Wang, Yueqiang; Sun, Lihua; Yuan, Yong
Abstract : A carbon dot-decorated reduced graphene oxide catalyst for the oxygen reduction reaction is developed via a combination of microbial reduction and hydrothermal treatment. Abstract : Catalysts for the oxygen reduction reaction (ORR) are crucial in fuel cells and metal–air batteries. The development of metal-free catalysts with high activity at low cost remains a great challenge. In this paper, a novel type of fluorescent carbon nanodots (CDs) supported by graphene have been developed through a microbial reduction process followed by a simple hydrothermal treatment. In the synthesis, microorganisms have the multi-function of simultaneously reducing and doping graphene oxide as reductants during the incubation process and producing CDs as self-sacrifice precursors during the hydrothermal treatment. Meanwhile, the CDs derived from bacterial cells were simultaneously self-packed on the microbially reduced graphene oxide (M-rGO) during the hydrothermal treatment to produce CD-coated M-rGO (CDs/M-rGO). Chemical analyses revealed that both CDs and M-rGO were doped with heteroatoms such as N, S, and P. Electrochemical characterization showed that the CDs/M-rGO hybrid had good catalytic properties with excellent long-term stability and resistance to methanol crossover for the ORR via a four-electron pathway in alkaline solution. The excellent electrocatalytic properties of CDs/M-rGO originate from the combined effect of heteroatom doping and numerous surface/edge defects that induce the high-density distribution of highly active and stable catalytic sites, and the strong coupling effects between CDs and graphene that can facilitate the charge transport and ionic motion during the ORR. This study presents a new approach to the production of inexpensive, graphene-based materials that exhibit high performance in the ORR.